2016
DOI: 10.1055/s-0036-1571953
|View full text |Cite
|
Sign up to set email alerts
|

Botulinum Toxin Treatment of Neuropathic Pain

Abstract: Neuropathic pain (NP), a common form of human pain, often poorly responds to analgesic medications. In this review the authors discuss the pathophysiology and conventional treatment of neuropathic pain and provide evidenced-based statements on the efficacy of botulinum neurotoxins (BoNTs) in this form of pain. The level of efficacy for BoNT treatment in each category of NP is defined according to the published guidelines of the American Academy of Neurology. The data indicate that BoNT treatment (most of the l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
17
0
9

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 43 publications
(28 citation statements)
references
References 95 publications
2
17
0
9
Order By: Relevance
“…In addition, only the responses to single doses of BoNT/A have been investigated in the current study and so it will be important in the future to investigate the long-term consequence of repeated injections. This is highly relevant as BoNT/A is increasingly being recommended for the treatment of a number of clinical disorders in which increased neuronal excitability is involved including idiopathic over-active bladder 42 , hemifacial spasms, cervical dystonia, various dyskinesias and spasticity following traumatic brain injury (reviewed by 43 ) and even for conditions such as migraine 44 and chronic pain 45 . BoNT/A is also currently being used in younger patients, most notably in children with cerebral palsy 46 .…”
Section: Discussionmentioning
confidence: 99%
“…In addition, only the responses to single doses of BoNT/A have been investigated in the current study and so it will be important in the future to investigate the long-term consequence of repeated injections. This is highly relevant as BoNT/A is increasingly being recommended for the treatment of a number of clinical disorders in which increased neuronal excitability is involved including idiopathic over-active bladder 42 , hemifacial spasms, cervical dystonia, various dyskinesias and spasticity following traumatic brain injury (reviewed by 43 ) and even for conditions such as migraine 44 and chronic pain 45 . BoNT/A is also currently being used in younger patients, most notably in children with cerebral palsy 46 .…”
Section: Discussionmentioning
confidence: 99%
“…The inhibitory effect of the BoNTs upon the release of acetylcholine at the neuromuscular junction is mostly responsible for the relief of pain caused by muscle spasms. In the case of neuropathic pain, it is currently believed that the analgesic effect of botulinum injections predominantly results from inhibition of pain neurotransmitters both at peripheral and at central sensory levels [5,6,71,72]. The peripheral injection of botulinum toxin-A into the muscle or close to peripheral nerve endings reduces the release of calcitonin gene related peptide, a major pain transmitter from trigeminal ganglion [73].…”
Section: Discussionmentioning
confidence: 99%
“…This is the primary reason it helps in conditions such as spasticity, cervical dystonia, blepharospasm, hemifacial spasm, and focal dystonias. BoNTs also alleviate neuropathic pain in animals through several mechanisms: blocking the release of pain mediators (glutamate, substance P, calcitonin gene related peptide (CRGP)) from peripheral terminals, dorsal root ganglia (DRG), and spinal cord neurons; decreasing local inflammation around nerve terminals; deactivation of sodium channels and decreasing sympathetic transmission [ 13 ]. Thus, there is an expanding literature on the role of BoNTs in pain conditions such as chronic migraine, post herpetic neuralgia, post-traumatic neuralgia, trigeminal neuralgia, and other neuropathic pain conditions.…”
Section: Introductionmentioning
confidence: 99%
“…These studies demonstrated mixed results with an unclear consensus. There is evidence that BoNTs may modulate afferent sensory fiber firing and thereby reduce the central sensitization and pain perception [ 13 ]. To date, the present trial is the largest double-blinded placebo-controlled study assessing the efficacy and safety of botulinum neurotoxin type A, namely incobotulinumtoxinA (IncoA) in refractory RLS patients.…”
Section: Introductionmentioning
confidence: 99%